Hubungan Academic Self-Efficacy dengan Academic Burnout pada Siswa Kelas X SMA Negeri 6 Palembang - Anshorryyah, Fadhilatul; Hadinata, Eko Oktapiya (Universitas Muhammadiyah Metro, 2023)
A student prone to academic burnout needs good academic self-efficacy to handle various academic demands. This study discusses the correlations between self-efficacy and burnout in class X students of SMA Negeri 6 Palembang. This research is quantitative correlational. The research participants consisted of 234 students of class X SMA Negeri 6 Palembang. The result of this study is that there is a significant negative relationship (r=-0.528, p<0.05). The higher the academic self-efficacy a student has, the lower the academic burnout the student feels. Vice versa, the lower the academic selfefficacy a student has, the higher the academic burnout thought by the student. The categorization results show that, in general, the research respondents are classified as having academic self-efficacy and academic burnout at a moderate level of (X = 58.5%) and (Y=68.8%).